Optimalisasi Pengelolaan Sampah di Kota Yogyakarta dalam Mewujudkan Tujuan Pembangunan Berkelanjutan - Anggiyanti, Destina Balqis; Evriyanti Simarangkir, Diny Widya; Kurniawati, Titis; Kamal, Ubaidillah (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Yogyakarta City, as one of Indonesia’s main tourist destinations, faces serious challenges in waste management due to the increasing population and tourist visits. These challenges include waste accumulation at final disposal sites (TPA), environmental pollution, and negative impacts on public health. Although the city government has launched the Zero Waste Action policy to encourage waste sorting at the household level, many residents still lack understanding of its implementation. This study aims to analyze waste management in Yogyakarta by gathering data from legal regulations and relevant literature. Optimizing waste management is crucial to achieving the Sustainable Development Goals (SDGs), particularly in the context of environmental sustainability and community quality of life. Effective management requires collaboration between the government and the community, as well as improvements in waste bank facilities and education on waste segregation. Without adequate knowledge, people tend to dispose of waste irresponsibly, potentially damaging the city’s image and environmental sustainability. Therefore, raising awareness about the importance of waste management must be pursued continuously to create a cleaner and healthier environment for future generations.